Picolyl amides of betulinic acid as antitumor agents causing tumor cell apoptosis - Bildziukevich, Uladzimir; Rárová, Lucie; Šaman, David; Wimmer, Zdeněk (European journal of medicinal chemistry, 2018)
A series of picolyl amides of betulinic acid (3a-3c and 6a-6c) was prepared and subjected to the cytotoxicity screening tests. Structure-activity relationships studies resulted in finding differences in biological activity in dependence on o-, m- and p-substitution of the pyridine ring in the target amides, when cytotoxicity data of 3a-3c and 6a-6c were obtained and compared. The amides 3b and 3a displayed cytotoxicity (given in the IC50 values) in G-361 (0.5 ± 0.1 μM and 2.4 ± 0.0 μM, respectively), MCF7 (1.4 ± 0.1 μM and 2.2 ± 0.2 μM, respectively), HeLa (2.4 ± 0.4 μM and 2.3 ± 0.5 μM, respectively) and CEM (6.5 ± 1.5 μM and 6.9 ± 0.4 μM, respectively) tumor cell lines, and showed weak effect in the normal human fibroblasts (BJ). Selectivity against all tested cancer cells was determined and compared to normal cells with therapeutic index (TI) between 7 and 100 for compounds 3a and 3b. The therapeutic index (TI = 100) was calculated for human malignant melanoma cell line (G-361) versus normal human fibroblasts (BJ). The cytotoxicity of other target amides (3c and 6a-6c) revealed lower effects than 3a and 3b in the tested cancer cell lines.
Keywords: Cell Line; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; apoptóza; Therapeutic index; Drug Screening Assays, Antitumor; Triterpenes; screeningové testy protinádorových léčiv; Pentacyclic Triterpenes; Cell Proliferation; Antineoplastic Agents; Amide; Cytotoxicity; Betulinic acid; pentacyklické triterpeny; Picolyl amine; protinádorové látky; amidy; vztahy mezi strukturou a aktivitou; Humans; Molecular Structure; triterpeny; Betulinic Acid; molekulární struktura; proliferace buněk; kyselina betulinová; Amides; buněčné linie; Structure-Activity Relationship; lidé; Apoptosis